2017
DOI: 10.1037/pag0000170
|View full text |Cite
|
Sign up to set email alerts
|

Route repetition and route reversal: Effects of age and encoding method.

Abstract: Previous research indicates age-related impairments in learning routes from a start location to a target destination. There is less research on age effects on the ability to reverse a learned path. The method used to learn routes may also influence performance. This study examined how encoding methods influence the ability of younger and older adults to recreate a route in a virtual reality environment in forward and reverse directions. Younger (n=50) and older (n=50) adults learned a route by either self-navi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

6
21
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 47 publications
6
21
1
1
Order By: Relevance
“…Taken together, the findings of the above studies suggest that spatial mental representations are related to the type of input used in the learning phase, and facilitated by learning from a map, but the type of recall task used to test spatial learning needs to be considered as well (Allison & Head, ; Yamamoto & DeGirolamo, ). This would seem to demonstrate an age‐related susceptibility to external factors in successful environment learning, in terms of both the type of input and the recall task.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Taken together, the findings of the above studies suggest that spatial mental representations are related to the type of input used in the learning phase, and facilitated by learning from a map, but the type of recall task used to test spatial learning needs to be considered as well (Allison & Head, ; Yamamoto & DeGirolamo, ). This would seem to demonstrate an age‐related susceptibility to external factors in successful environment learning, in terms of both the type of input and the recall task.…”
Section: Introductionmentioning
confidence: 98%
“…This would suggest that map‐reading skills are better preserved with ageing than exploratory navigation skills. Further, Allison and Head () examined route learning from real navigation and from a map, testing older adults’ recall on route repetition and route reversal tasks. They found that learning from a map was more effortful for older adults.…”
Section: Introductionmentioning
confidence: 99%
“…relatively easy access to, virtual environment technology has led most research groups to design and develop their own navigational tasks and protocols, which makes it difficult to compare findings across studies and research groups. As a consequence, normative data for the most popular or frequent navigational tasks, such as route learning (e.g., Allison & Head, 2017;Head & Isom, 2010;Moffat, Zonderman, & Resnick, 2001), landmark sequence test (e.g., Taillade, N'Kaoua, & Sauzéon, 2016;Taillade et al, 2013), landmark recognition test (e.g., Zhong & Kozhevnikov, 2016;Zhong & Moffat, 2016), and cognitive mapping or landmark placement (e.g., Iaria et al, 2009;Liu, Levy, Barton, & Iaria, 2011), are missing at present. Here we begin to address these problems by developing and evaluating three different route-learning tasks (1) that are based on established and published earlier navigation protocols (Head & Isom, 2010;Waller & Lippa, 2007;Wiener, de Condappa, Harris, & Wolbers, 2013;Wiener et al, 2012), (2) that are easy to adapt to address specific research questions, (3) that we make freely available to other research groups (https://osf.io/mx52y/), and (4) that may be of broader interest to researchers engaged in clinical research with various populations.…”
mentioning
confidence: 99%
“…Such knowledge contains information about the spatial relationships between locations or landmarks and has been widely referred to as allocentric (Gramann, 2013;Wolbers & Wiener, 2014;Zhong & Kozhevnikov, 2016). To our knowledge, only a few studies have addressed the effects of cognitive aging on route repetition and route retracing (Allison & Head, 2017;Wiener et al, 2012). Although younger participants outperformed the older age group in both route repetition and route retracing, the performance differences were particularly pronounced in retracing, and in contrast to the repetition condition, older adults did not exhibit significant performance improvement in the retracing condition over the course of the experiment.…”
mentioning
confidence: 99%
“…Even though spatial navigation seems effortless at the behavioral level, it is a multimodal activity that draws upon a multitude of cognitive and neural resources (Moffat, 2009 , 2016 ; Wolbers and Hegarty, 2010 ; Wolbers, 2015 ; Zhong and Kozhevnikov, 2016 ; Lester et al, 2017 ). Numerous behavioral studies of spatial navigation in the cognitive aging literature have identified age-related declines or deficits in navigation strategies (Moffat and Resnick, 2002 ; Bohbot et al, 2012 ; Harris et al, 2012 ; Wiener et al, 2013 ; Harris and Wolbers, 2014 ; Colombo et al, 2017 ; Zhong et al, 2017 ), associative learning/memory (Head and Isom, 2010 ; Liu et al, 2011 ; Wiener et al, 2012 , 2013 ; Zhong and Moffat, 2016 ; Allison and Head, 2017 ; O’Malley et al, 2018 ), and working memory (Mahmood et al, 2009 ; Taillade et al, 2013a , b , 2016 ; Ariel and Moffat, 2018 ). Complementary neuroimaging studies that investigated age-related declines in spatial navigation performance and memory have largely linked them to age-related reduction in the volume or activation of the hippocampus (e.g., Driscoll et al, 2003 , 2005 ; Astur et al, 2006 ; Moffat et al, 2006 , 2007 ; Antonova et al, 2009 ; Yuan et al, 2014 ; Daugherty et al, 2015 , 2016 ), a region that has long been proposed as the neural basis of a “cognitive map” (O’Keefe and Dostrovsky, 1971 ; O’Keefe and Nadel, 1978 ).…”
Section: Introductionmentioning
confidence: 99%